Adhesive tapes and articles

JP7632515B2Active Publication Date: 2025-02-19DIC CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023088542
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-05-30
Publication Date
2025-02-19
Estimated Expiration
2038-09-07

AI Technical Summary

Benefits of technology

【0009】 本発明の粘着テープは、優れた剥離強度、優れたせん断接着強度及び優れた初期タック性を同時に満たし、更に地球環境に優しいという特性を有する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007632515000001
    Figure 0007632515000001
  • Figure 0007632515000002
    Figure 0007632515000002
Patent Text Reader

Abstract

To provide an adhesive tape which simultaneously satisfies excellent peel strength, excellent shear adhesive strength and excellent initial tackiness, and is further friendly to the global environment.SOLUTION: An adhesive tape has an adhesive layer which contains 50 pts.mass to 150 pts.mass of a tackifier resin with respect to 100 pts.mass of an adhesive resin solid content and has a temperature indicating a peak value of a loss tangent (tanδ) at a frequency of 1 Hz of -10°C to 50°C, and has a biomass degree of 45% or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an adhesive tape that can be used in the manufacturing process of various products, including electronic devices. [Background technology]

[0002] Adhesive tapes are widely used in the manufacturing of various products, including electronic devices and automobiles.

[0003] The adhesive tape generally has adhesive strength (peeling strength) and tack (adhesiveness) as basic properties (for example, Patent Documents 1 to 3), but depending on the application of the adhesive tape, other properties may be required. For example, when used for a large desktop display, the display is frameless, and the tape has a small area to support a heavy display such as a liquid crystal module, so high shear adhesive strength is required. An example of a tape having high shear adhesive strength is a thermal adhesive tape, but it is difficult to use because an additional process of applying heat is required and heat or excessive pressure cannot be applied depending on the location or parts. Although the above Patent Documents 1 to 3 have basic properties such as the above adhesive strength and tack at a practical level, they have not yet demonstrated sufficient performance in terms of shear adhesive strength.

[0004] Furthermore, in recent years, as interest in environmental issues such as global warming has increased, there has been strong social demand, particularly for chemical manufacturers, to use plant-derived materials as alternatives to conventional petroleum-derived materials. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent Publication No. 2005-307063 [Patent Document 2] Patent Publication No. 2006-206624 [Patent Document 3] Patent Publication No. 2009-102467 Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide an adhesive tape which simultaneously satisfies excellent peel strength, excellent shear adhesive strength and excellent initial tackiness, and which is also environmentally friendly. [Means for solving the problem]

[0007] The present inventors have found that the above problems can be solved by an adhesive tape that contains a tackifier resin in a specific ratio, has an adhesive layer in which the temperature showing the peak value of the loss tangent (tan δ) is in a specific range, and has a biomass degree of a specific value or more.

[0008] In other words, the present invention relates to an adhesive tape which contains 50 parts by mass to 150 parts by mass of a tackifier resin per 100 parts by mass of adhesive resin solid content, has an adhesive layer having a temperature showing a peak value of loss tangent (tan δ) at a frequency of 1 Hz ranging from -10°C to 50°C, and has a biomass degree of 45% or more. Effect of the Invention

[0009] The pressure-sensitive adhesive tape of the present invention has excellent peel strength, excellent shear adhesive strength and excellent initial tackiness at the same time, and further has the property of being environmentally friendly. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The adhesive tape of the present invention is characterized in that it contains 50 parts by mass to 150 parts by mass of a tackifier resin per 100 parts by mass of adhesive resin solid content, has an adhesive layer having a temperature showing a peak value of loss tangent (tan δ) at a frequency of 1 Hz in the range of -10°C to 50°C, and has a biomass degree of 45% or more.

[0011] The embodiment of the pressure-sensitive adhesive tape includes, for example, a pressure-sensitive adhesive tape having the pressure-sensitive adhesive layer directly or via another layer on one or both sides of a substrate, and a so-called substrate-less pressure-sensitive adhesive tape composed only of the pressure-sensitive adhesive layer. The pressure-sensitive adhesive layer may be a single layer or multiple layers made of the same or different compositions. When the tape of the present invention is used to fix two or more adherends that constitute, for example, electronic devices, it is preferable to use it in the embodiment of a double-sided pressure-sensitive adhesive tape having pressure-sensitive adhesive layers on both sides of a substrate. When the tape is used for labels, it is preferable to use it in the embodiment of a single-sided pressure-sensitive adhesive tape having a pressure-sensitive adhesive layer on one side of a substrate. The pressure-sensitive adhesive tape of the present invention may be stored with a release film laminated on the surface of the pressure-sensitive adhesive layer.

[0012] The pressure-sensitive adhesive tape of the present invention has a biomass ratio of 45% or more. Note that, in the present invention, the biomass ratio refers to the content (mass%) of carbon originating from biomass in the total carbon, calculated by measurement according to ASTM-D6866-18.

[0013] The thickness of the pressure-sensitive adhesive tape of the present invention is preferably in the range of 5 μm to 500 μm, more preferably in the range of 7 μm to 350 μm, still more preferably in the range of 10 μm to 200 μm, still more preferably in the range of 15 μm to 100 μm, and even more preferably in the range of 20 μm to 60 μm, in order to simultaneously satisfy excellent peel strength, excellent shear adhesive strength, and excellent initial tackiness, and to contribute to the thinning of electronic devices and the like.

[0014] (Adhesive layer) The adhesive layer constituting the adhesive tape of the present invention preferably has a thickness in the range of 5 μm to 200 μm, more preferably 10 μm to 100 μm, and even more preferably 20 μm to 50 μm, in order to simultaneously satisfy excellent peel strength, excellent shear adhesive strength, and excellent initial tackiness, and to contribute to thinner electronic devices and the like.

[0015] The adhesive layer constituting the adhesive tape of the present invention is formed from an adhesive composed of an adhesive resin and a tackifier resin. The adhesive layer preferably has a biomass degree of 45% or more. The temperature at which the adhesive resin exhibits a peak value of loss tangent (tan δ) at a frequency of 1 Hz is preferably low so that a large amount of the tackifier resin can be added, and specifically, is preferably −50° C. to 20° C., more preferably −45° C. to 15° C., and even more preferably −40° C. to 10° C. Examples of the adhesive include (meth)acrylic adhesives, urethane adhesives, synthetic rubber adhesives, natural rubber adhesives, and silicone adhesives. In terms of weather resistance and heat resistance, however, (meth)acrylic adhesives are preferred, in which an acrylic copolymer consisting of (meth)acrylate alone or a copolymer of (meth)acrylate and other monomers is used as a base polymer, and a tackifier resin and, if necessary, additives such as a crosslinking agent are blended.

[0016] The loss tangent (tan δ) at a frequency of 1 Hz is calculated from the storage modulus (G') and loss modulus (G") obtained by dynamic viscoelasticity measurement using temperature dispersion, using the formula tan δ = G" / G'. In measuring dynamic viscoelasticity, a viscoelasticity tester (manufactured by TA Instruments Japan, product name: ARES G2) is used to sandwich a pressure-sensitive adhesive layer formed to a thickness of approximately 2 mm between parallel disks with a diameter of 8 mm, which is the measuring section of the tester, and the storage modulus (G') and loss modulus (G") are measured at a frequency of 1 Hz from -50°C to 150°C.

[0017] The acrylic copolymer preferably has an alkyl (meth)acrylate monomer as a main monomer component, and the alkyl group of the alkyl (meth)acrylate monomer may be linear or branched. The alkyl (meth)acrylate monomer may be, for example, methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, n-hexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, isostearyl (meth)acrylate, isobornyl (meth)acrylate, cyclohexyl (meth)acrylate, and other alkyl (meth)acrylates having 1 to 18 carbon atoms in the alkyl group. One or more of these may be used, but it is preferable to use two or more. Among these, (meth)acrylate monomers having an alkyl group with 2 to 16 carbon atoms are preferred, and (meth)acrylate monomers having 3 to 14 carbon atoms are more preferred. Use of the above monomers is preferred in that excellent shear adhesive strength and excellent initial tackiness are simultaneously exhibited, and the addition of a tackifier becomes easy.

[0018] The content of one or more selected from the group consisting of alkyl (meth)acrylate monomers relative to the total amount of acrylic monomers usable in producing the acrylic copolymer is preferably 70 mass% or more, more preferably 75 to 99 mass%, and even more preferably 80 to 96 mass%.

[0019] In addition, the acrylic copolymer is preferably copolymerized with a highly polar vinyl monomer, and examples of the highly polar vinyl monomer include a carboxyl group-containing vinyl monomer, a hydroxyl group-containing vinyl monomer, an amide group-containing vinyl monomer, etc., and one or more of these are used. Among them, a carboxyl group-containing monomer and a hydroxyl group-containing vinyl monomer are preferably used because the adhesiveness of the pressure-sensitive adhesive can be easily adjusted to a suitable range.

[0020] Examples of the carboxyl group-containing vinyl monomer that can be used include acrylic acid, methacrylic acid, itaconic acid, maleic acid, β-carboxyethyl acrylic acid, (meth)acrylic acid dimer, crotonic acid, and ethylene oxide-modified succinic acid acrylate. Among these, it is preferable to use acrylic acid as a copolymerization component in order to develop excellent initial tackiness.

[0021] The content of the carboxyl group-containing vinyl monomer relative to the total amount of acrylic monomers used in producing the acrylic copolymer is 1 to 30 mass%, more preferably 2 to 20 mass%, and more preferably 3 to 15 mass%, in order to simultaneously exhibit excellent peel strength, excellent shear adhesive strength, and excellent initial tackiness.

[0022] Examples of the hydroxyl group-containing vinyl monomer that can be used include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 6-hydroxyhexyl (meth)acrylate. Among these, 4-hydroxybutyl (meth)acrylate is preferred in that it simultaneously exhibits excellent peel strength, excellent shear adhesive strength, and excellent initial tackiness.

[0023] The content of the hydroxyl group-containing vinyl monomer relative to the total amount of acrylic monomers that can be used in producing the acrylic copolymer is 1.0 mass% or less, preferably 0.01 to 0.85 mass%, more preferably 0.02 to 0.7 mass%, more preferably 0.03 to 0.5 mass%, and even more preferably 0.04 to 0.3 mass%, and is preferably 0.05 to 0.2 mass% in order to simultaneously exhibit excellent shear adhesive strength and excellent initial tackiness.

[0024] Examples of the amide group-containing vinyl monomer include N-vinylpyrrolidone, N-vinylcaprolactam, acryloylmorpholine, acrylamide, and N,N-dimethylacrylamide.

[0025] Other highly polar vinyl monomers include vinyl acetate, ethylene oxide modified succinic acid acrylate, sulfonic acid group-containing monomers such as 2-acrylamido-2-methylpropanesulfonic acid, and terminal alkoxy modified (meth)acrylates such as 2-methoxyethyl (meth)acrylate and 2-phenoxyethyl (meth)acrylate.

[0026] The content of the highly polar vinyl monomer relative to the total amount of acrylic monomers that can be used in producing the acrylic copolymer is preferably 0.2 to 15 mass%, more preferably 0.4 to 10 mass%, and is preferably 0.5 to 6 mass% in order to simultaneously exhibit excellent peel strength, excellent shear adhesive strength, and excellent initial tackiness.

[0027] The acrylic copolymer can be obtained by copolymerization by known polymerization methods such as solution polymerization, bulk polymerization, suspension polymerization, and emulsion polymerization, but solution polymerization and bulk polymerization are preferred in terms of the water resistance of the adhesive. The polymerization initiation method can be arbitrarily selected from thermal initiation methods using peroxide-based thermal polymerization initiators such as benzoyl peroxide and lauroyl peroxide, and azo-based thermal polymerization initiators such as azobisisobutylnitrile, ultraviolet irradiation initiation methods using acetophenone-based, benzoin ether-based, benzil ketal-based, acylphosphine oxide-based, benzoin-based, and benzophenone-based photopolymerization initiators, and electron beam irradiation methods.

[0028] The molecular weight of the acrylic copolymer is preferably 400,000 or more, more preferably 420,000 to 1,500,000, in terms of standard polystyrene, as measured by gel permeation chromatography (GPC), and is preferably 450,000 to 1,200,000, in order to simultaneously exhibit excellent peel strength, excellent shear adhesive strength, and excellent initial tackiness.

[0029] Here, the molecular weight is measured by the GPC method using a GPC apparatus (HLC-8329GPC) manufactured by Tosoh Corporation, and is expressed as a standard polystyrene equivalent value. The measurement conditions are as follows.

[0030] Sample concentration: 0.5% by mass (THF solution) Sample injection volume: 100 μL Eluent:THF Flow rate: 1.0mL / min Measurement temperature: 40℃ Column: 4 TSKgel GMHXL Guard column: TSKgel HXL-H Detector: Differential refractometer Standard polystyrene molecular weight: 10,000 to 20 million (Tosoh Corporation)

[0031] The adhesive used in the adhesive tape of the present invention preferably forms a three-dimensional crosslinked structure in order to improve cohesive strength. As an index of crosslinked structure formation, the gel fraction represented by the insoluble matter after immersion for 24 hours in toluene, which is a good solvent for (meth)acrylic adhesives, is used. In this case, it is preferably 10 to 50 mass%, more preferably 15 to 40 mass%. If the gel fraction is less than 10 mass%, the cohesive strength in the shear direction is insufficient, and if it exceeds 50 mass%, the initial tackiness is reduced.

[0032] The gel fraction is calculated by the following formula. Gel fraction (mass%)={(mass of adhesive after immersion in toluene) / (mass of adhesive before immersion in toluene)}×100

[0033] The adhesive layer of the adhesive tape of the present invention contains 50 to 150 parts by mass of a tackifier resin per 100 parts by mass of adhesive resin solids, preferably 60 to 125 parts by mass, more preferably 80 to 110 parts by mass.

[0034] Examples of the tackifier resin include rosin-based tackifier resins, which are plant-derived tackifier resins, terpene-based tackifier resins, terpene phenol-based tackifier resins, etc. The tackifier resins may be used alone or in combination of two or more kinds.

[0035] Examples of rosin-based tackifying resins include unmodified rosins (raw rosins) such as gum rosin, wood rosin, and tall oil rosin; modified rosins obtained by modifying these unmodified rosins through polymerization, disproportionation, hydrogenation, or the like (polymerized rosin, stabilized rosin, disproportionated rosin, fully hydrogenated rosin, partially hydrogenated rosin, and other chemically modified rosins); and various rosin derivatives. Examples of the rosin derivatives include rosin phenolic resins obtained by adding phenol to rosins (unmodified rosin, modified rosin, various rosin derivatives, etc.) using an acid catalyst and thermally polymerizing the resulting mixture; rosin ester resins such as rosin ester compounds (unmodified rosin esters) obtained by esterifying unmodified rosin with alcohols, and modified rosin ester compounds (polymerized rosin ester, stabilized rosin ester, disproportionated rosin ester, fully hydrogenated rosin ester, partially hydrogenated rosin ester, etc.) obtained by esterifying modified rosins such as polymerized rosin, stabilized rosin ester, disproportionated rosin ester, fully hydrogenated rosin ester, partially hydrogenated rosin ester, etc.) with alcohols; unsaturated fatty acid modified rosin-based resins obtained by modifying rosin or modified rosin (polymerized rosin, stabilized rosin, disproportionated rosin, fully hydrogenated rosin, partially hydrogenated rosin, etc.) with unsaturated fatty acid; unsaturated fatty acid modified rosin ester-based resins obtained by modifying rosin ester-based resins with unsaturated fatty acid; rosin alcohol-based resins obtained by reducing the carboxyl groups in unmodified rosin, modified rosin (polymerized rosin, stabilized rosin, disproportionated rosin, fully hydrogenated rosin, partially hydrogenated rosin, etc.), unsaturated fatty acid modified rosin-based resins, and unsaturated fatty acid modified rosin ester-based resins; and metal salts of rosin-based resins (particularly rosin ester-based resins) such as unmodified rosin, modified rosin, and various rosin derivatives.

[0036] Examples of terpene-based tackifying resins include terpene-based resins such as α-pinene polymers, β-pinene polymers, and dipentene polymers, as well as modified terpene-based resins obtained by modifying these terpene-based resins (phenol-modified, aromatic-modified, hydrogen-modified, hydrocarbon-modified, etc.) (e.g., terpene-phenolic resins, styrene-modified terpene resins, aromatic-modified terpene resins, hydrogenated terpene resins, etc.). As the tackifier resin, a rosin-based tackifier resin or a terpene-based tackifier resin can be suitably used.

[0037] The tackifier resin preferably has a biomass degree of 50% or more, more preferably 60% or more, more preferably 70% or more, more preferably 80% or more, more preferably 90% or more, and most preferably 95% to 100%. The use of the tackifier resin is preferable in that it simultaneously exhibits excellent peel strength, excellent shear adhesive strength, and excellent initial tackiness, and also improves the biomass degree.

[0038] The softening point of the tackifier resin is not particularly limited, but is from 20 to 180° C., and preferably from 25 to 140° C. Two or more types of the tackifier resin may be used in combination.

[0039] The pressure-sensitive adhesive layer used in the pressure-sensitive adhesive tape of the present invention, which is composed of the pressure-sensitive adhesive resin and the tackifier resin, preferably has a temperature at which the loss tangent (tan δ) at a frequency of 1 Hz peaks, is -10°C to 50°C. By setting the peak loss tangent of the pressure-sensitive adhesive layer within this range, it becomes easier to impart good adhesion to the adherend at room temperature. Furthermore, from the viewpoint of improving the shear adhesive strength, the temperature is more preferably -5°C to 45°C, and even more preferably 5°C to 40°C.

[0040] The adhesive constituting the adhesive layer may contain additives such as plasticizers, softeners, antioxidants, flame retardants, fillers such as glass or plastic fibers / balloons, beads, metals, metal oxides, metal nitrides, etc., colorants such as pigments and dyes, leveling agents, thickeners, water repellents, and defoamers.

[0041] The adhesive constituting the adhesive layer preferably contains a solvent in order to maintain good coating workability, etc. Examples of the solvent that can be used include toluene, xylene, ethyl acetate, butyl acetate, acetone, methyl ethyl ketone, and hexane. When preparing a water-based adhesive composition, water or an aqueous solvent mainly composed of water can be used.

[0042] (base material) The pressure-sensitive adhesive tape of the present invention may be provided with a substrate. As the substrate, for example, a nonwoven fabric substrate or a resin film may be used. Examples of the nonwoven fabric substrate include nonwoven fabrics obtained using chemical fibers such as Manila hemp, wood pulp, rayon, acetate fiber, polyester fiber, vinylon fiber (polyvinyl alcohol fiber), polyamide fiber, and mixtures thereof. Among these, it is more preferable to use a nonwoven fabric produced using 50% or more of raw materials derived from plants.

[0043] In addition, sheets or films obtained using polyesters such as the above-mentioned polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate, and polyethylene furanoate, polyolefins, polyacrylates, polyvinyl chloride, polyethylene, polypropylene ethylene vinyl alcohol, polyurethane, polyamide, and polyimide, and non-foamed film substrates such as glass can be used. The surfaces of these substrates may be subjected to antistatic treatment, corona treatment, and the like. In addition, a foam substrate may be used as the substrate. For example, polyolefin foam, polyurethane foam, acrylic foam, other rubber foam, etc. may be used as the foam substrate. The surface of the foam substrate may be subjected to antistatic treatment, corona treatment, etc. Among them, it is more preferable to use the resin film produced using 20% ​​or more of raw materials derived from plants.

[0044] (Manufacturing method) Examples of manufacturing methods for the adhesive tape of the present invention, in the case of an adhesive tape having a substrate (core), include a manufacturing method (direct method) in which the adhesive composition is applied to one or both sides of the substrate and dried or the like, or a manufacturing method (transfer method) in which the adhesive composition is applied to the surface of a release liner and dried or the like to form an adhesive layer, and then the adhesive layer is transferred to one or both sides of the substrate. Examples of a method for producing the substrate-less pressure-sensitive adhesive tape include a method in which a pressure-sensitive adhesive composition is applied to the surface of a release liner and then dried to form a pressure-sensitive adhesive layer.

[0045] Examples of the method for applying the pressure-sensitive adhesive composition to the substrate or release liner include methods using an applicator, roll coater, gravure coater, reverse coater, spray coater, air knife coater, die coater, and the like. The pressure-sensitive adhesive composition may be dried, for example, for 30 seconds to 10 minutes at 50° C. to 140° C. After drying, the composition may be further aged at a temperature in the range of 30° C. to 50° C. in order to promote the curing reaction. EXAMPLES

[0046] The present invention will now be described in more detail with reference to examples.

[0047] [Adjustment example 1] A reaction vessel equipped with a stirrer, a reflux condenser, a nitrogen inlet tube, and a thermometer was charged with 59.9 parts by mass of n-butyl acrylate, 36 parts by mass of 2-ethylhexyl acrylate, 4 parts by mass of acrylic acid, 0.1 parts by mass of 4-hydroxybutyl acrylate, and 200 parts by mass of ethyl acetate, and the mixture was held at 72°C for 4 hours with stirring, and then at 75°C for 5 hours.

[0048] Next, 2 parts by mass of a solution of 2,2'-azobis(2-methylbutyronitrile) previously dissolved in ethyl acetate (solid content 0.1% by mass) was added to the mixture, and the mixture was kept at 72°C for 4 hours under stirring, and then at 75°C for 5 hours. Next, the mixture was diluted with 98 parts by mass of ethyl acetate and filtered through a 200 mesh wire screen to obtain a solution of an acrylic copolymer (A-1) having a weight average molecular weight of 1,040,000.

[0049] The acrylic copolymer (A-1) solution was mixed with 15 parts by mass of Harima Chemical Co., Ltd.'s "Haritac PCJ" (biomass content: 95%), 85 parts by mass of Arakawa Chemical Industries Co., Ltd.'s "Super Ester A-100" (biomass content: 100%), and an adduct of tolylene diisocyanate and trimethylolpropane (DIC Corporation's "Burnock D-40", hereinafter abbreviated as "D-40") to obtain an adhesive (P-1) (biomass content: 49.6%) with a gel fraction of 39.9%.

[0050] [Adjustment example 2] The acrylic copolymer (A-1) was blended with 15 parts of Arakawa Chemical Industries' "Super Ester L" (biomass content: 90.7%), 45 parts of Arakawa Chemical Industries' "Super Ester A-75" (biomass content: 91%), 30 parts of Super Ester A-100, 10 parts of Haritac PCJ, and D-40 to obtain an adhesive (P-2) (biomass content: 47.0%) with a gel fraction of 29.1%.

[0051] [Adjustment example 3] An acrylic copolymer (A-2) solution having a weight average molecular weight of 500,000 was obtained in the same manner as in Preparation Example 1, except that the amounts of 2-ethylhexyl acrylate, acrylic acid, and β-carboxyethyl acrylate were changed to 96.4 parts by mass, 1.2 parts by mass, and 2.4 parts by mass, respectively. The acrylic copolymer (A-2) solution was mixed with 85 parts by mass of Super Ester A-100, 15 parts by mass of Haritac PCJ, and a 2% ethyl acetate solution of an epoxy-based crosslinking agent (Tetrad C manufactured by Mitsubishi Gas Chemical Co., Ltd.) to obtain an adhesive (P-3) with a gel fraction of 37.8% (biomass content: 49.6%).

[0052] [Adjustment example 4] An acrylic copolymer (A-3) solution having a weight average molecular weight of 510,000 was obtained in the same manner as in Preparation Example 1, except that the amounts of n-butyl acrylate, 2-ethylhexyl acrylate, acrylic acid, and 4 parts by mass were changed to 59 parts by mass, 36 parts by mass, 4 parts by mass, and 0.1 parts by mass of 4-hydroxybutyl acrylate. The acrylic copolymer (A-3) solution was mixed with 85 parts by mass of Super Ester A-100, 15 parts by mass of Haritac PCJ, and D-40 to obtain an adhesive (P-4) with a gel fraction of 30.6% (biomass content: 49.6%).

[0053] [Adjustment example 5] An acrylic copolymer (A-4) solution having a weight average molecular weight of 660,000 was obtained in the same manner as in Preparation Example 1, except that the components were changed to 54.9 parts by mass of n-butyl acrylate, 44 parts by mass of 2-ethylhexyl acrylate, 1 part by mass of acrylic acid, and 0.1 parts by mass of 4-hydroxybutyl acrylate. The acrylic copolymer (A-4) solution was mixed with 85 parts by mass of Super Ester A-100, 15 parts by mass of Haritac PCJ, and D-40 to obtain an adhesive (P-5) with a gel fraction of 25.5% (biomass content: 49.6%).

[0054] [Example 1] The adhesive (P-1) obtained in Preparation Example 1 was applied to the release-treated surface of a release liner (a 75 μm-thick polyethylene terephthalate film with one side treated for release) and dried at 80° C. for 5 minutes to produce an adhesive layer 50 μm thick. Thereafter, the mixture was aged in an environment of 40° C. for 48 hours to obtain a double-sided adhesive tape (T-1).

[0055] [Example 2] A double-sided adhesive tape (T-2) having a thickness of 50 μm was obtained in the same manner as in Example 1, except that the adhesive (P-2) was used instead of the adhesive (P-1).

[0056] [Example 3] A double-sided adhesive tape (T-3) having a thickness of 50 μm was obtained in the same manner as in Example 1, except that the adhesive (P-3) was used instead of the adhesive (P-1).

[0057] [Example 4] A double-sided adhesive tape (T-4) having a thickness of 50 μm was obtained in the same manner as in Example 3, except that the adhesive (P-4) was used instead of the adhesive (P-1).

[0058] [Example 5] A double-sided adhesive tape (T-5) having a thickness of 50 μm was obtained in the same manner as in Example 3, except that the adhesive (P-5) was used instead of the adhesive (P-1).

[0059] [Comparative Adjustment Example 1] The acrylic copolymer (A-4) was mixed with 85 parts by mass of "FTR6100" manufactured by Mitsui Chemicals, Inc., 15 parts by mass of "FTR6125" manufactured by Mitsui Chemicals, Inc., and D-40 to obtain an adhesive (Q-1) (biomass content: 0%) with a gel fraction of 39.1%.

[0060] [Comparative Adjustment Example 2] A reaction vessel equipped with a stirrer, a reflux condenser, a nitrogen inlet tube, and a thermometer was charged with 61.9 parts by mass of 2-ethylhexyl acrylate, 26 parts by mass of isobornyl acrylate, 12 parts by mass of acrylic acid, 0.1 part by mass of 4-hydroxybutyl acrylate, and 200 parts by mass of ethyl acetate, and the mixture was held at 72°C for 4 hours with stirring, and then at 75°C for 5 hours.

[0061] Next, 2 parts by mass of a solution of 2,2'-azobis(2-methylbutyronitrile) previously dissolved in ethyl acetate (solid content 0.1% by mass) was added to the mixture, and the mixture was kept at 72°C for 4 hours under stirring, and then at 75°C for 5 hours. Next, the mixture was diluted with 98 parts by mass of ethyl acetate and filtered through a 200 mesh wire screen to obtain a solution of an acrylic copolymer (B-1) having a weight average molecular weight of 300,000. D-40 was added to the acrylic copolymer (B-1) solution to obtain a pressure sensitive adhesive (Q-2) (biomass content: 21%) with a gel fraction of 6.9%.

[0062] [Comparative Adjustment Example 3] A reaction vessel equipped with a stirrer, a reflux condenser, a nitrogen inlet tube, and a thermometer was charged with 97.9 parts by mass of n-butyl acrylate, 2 parts by mass of acrylic acid, 0.1 parts by mass of 4-hydroxybutyl acrylate, and 200 parts by mass of ethyl acetate, and the mixture was held at 72°C for 4 hours with stirring, and then at 75°C for 5 hours.

[0063] Next, 4 parts by mass of a solution of 2,2'-azobis(2-methylbutyronitrile) previously dissolved in ethyl acetate (solid content 0.1% by mass) was added to the mixture, and the mixture was held at 72°C for 4 hours under stirring, and then held at 75°C for 5 hours.

[0064] Next, the mixture was diluted with 98 parts by mass of ethyl acetate and filtered through a 200 mesh wire screen to obtain a solution of an acrylic copolymer (B-2) having a weight average molecular weight of 1,060,000. D-40 was added to the acrylic copolymer (B-2) solution to obtain a pressure sensitive adhesive (Q-3) with a gel fraction of 42.8% (biomass ratio: 19.8%).

[0065] [Comparative Adjustment Example 4] The acrylic copolymer (A-1) solution was mixed with 85 parts by mass of Super Ester L, 15 parts by mass of Haritac PCJ, and D-40 to obtain an adhesive (Q-4) with a gel fraction of 27.4% (biomass content: 45.4%).

[0066] [Comparative Adjustment Example 5] The acrylic copolymer (A-1) solution was mixed with 85 parts by mass of Super Ester A-100, 65 parts by mass of Haritac PCJ, and D-40 to obtain an adhesive (Q-5) with a gel fraction of 15.0% (biomass content: 58.7%).

[0067] [Comparative Example 1] The adhesive (Q-1) obtained in Comparative Preparation Example 1 was applied to the release-treated surface of a release liner (a 75 μm-thick polyethylene terephthalate film with one side treated for release) and dried at 80° C. for 5 minutes to produce an adhesive layer 50 μm thick. Thereafter, the mixture was aged in an environment of 40° C. for 48 hours to obtain a double-sided adhesive tape (U-1).

[0068] [Comparative Example 2] A double-sided adhesive tape (U-2) having a thickness of 50 μm was obtained in the same manner as in Comparative Example 1, except that the adhesive (Q-2) was used instead of the adhesive (Q-1).

[0069] [Comparative Example 3] A double-sided adhesive tape (U-3) having a thickness of 50 μm was obtained in the same manner as in Comparative Example 1, except that the adhesive (Q-3) was used instead of the adhesive (Q-1).

[0070] [Comparative Example 4] A double-sided adhesive tape (U-4) having a thickness of 50 μm was obtained in the same manner as in Comparative Example 1, except that the adhesive (Q-4) was used instead of the adhesive (Q-1).

[0071] [Comparative Example 5] A double-sided adhesive tape (U-5) having a thickness of 50 μm was obtained in the same manner as in Comparative Example 1, except that the adhesive (Q-5) was used instead of the adhesive (Q-1).

[0072] [Method for measuring peel strength] The release liner on one side of each of the double-sided adhesive tapes obtained in the Examples and Comparative Examples was peeled off, the tape was backed with a 25 μm thick PET film, and cut to a width of 25 mm to prepare a test piece. The release liner on the other side of the test piece was peeled off and the other side was attached to the surface of a 2 mm thick stainless steel (SUS) plate (adhesive area 25 mm x 80 mm), and then the upper surface was pressed by rolling a 2 kg roll back and forth once to obtain a patch. The patch was left for 1 hour in an atmosphere of 23° C. and 50% RH. Next, the 180 degree peel strength (N / 25 mm) of the test piece constituting the patch was measured in an atmosphere of 23° C. and 50% RH in accordance with JIS Z0237.

[0073] A: The peel strength was 25N / 25mm or more. B: The peel strength was 12.5 N / 25 mm or more and less than 25 N / 25 mm. C: The peel strength was less than 12.5 N / mm. D: Stick-slip (SS) occurred and measurement was not possible.

[0074] [Method of measuring shear adhesive strength] The double-sided adhesive tapes obtained in the Examples and Comparative Examples were cut into 10 mm squares to prepare test pieces. The release liner on one side of the test piece was peeled off and the piece was attached to the surface of a 2 mm thick stainless steel (SUS) plate, and then the release liner on the other side was peeled off and a 25 mm wide, 80 mm long, 50 μm thick stainless steel foil was attached, and the piece was pressed against the plate by rolling it back and forth once with a 2 kg roll to obtain a patch. The patch was left for 24 hours in an atmosphere of 23° C. and 50% RH. Next, the stainless steel foil and stainless steel plate of the test piece constituting the adhesive were pulled at a speed of 10 mm / min in an atmosphere of 23° C. and 50% RH, and the strength at which the stainless steel foil peeled off was measured.

[0075] A: The shear adhesive strength was 2 MPa or more. B: The shear adhesive strength was 1.5 MPa or more and less than 2.0 MPa. C: The shear adhesive strength was 1.0 MPa or more and less than 1.5 MPa. D: The shear adhesive strength was less than 1.0 MPa.

[0076] [Evaluation method for initial tackiness] The adhesive surface of each of the double-sided adhesive tapes obtained in the Examples and Comparative Examples was evaluated for feel when touched with a finger according to the following criteria. A: When you touch the adhesive surface of the tape, it has a strong tacky feel. B: When you touch the adhesive surface of the tape, there is a slight tackiness. C: There is almost no tackiness when you touch the adhesive surface of the tape.

[0077] [Table 1]

[0078] [Table 2]

[0079] From the above results, it is understood that Examples 1 to 5 of the present invention have good properties in terms of peel strength, initial tackiness, and shear adhesive strength, whereas Comparative Examples 1 to 5 are inferior in at least one of the above properties.

Claims

1. An adhesive layer containing 50 to 150 parts by mass of a rosin-based tackifier resin relative to 100 parts by mass of adhesive resin solids, having a temperature showing a peak value of loss tangent (tan δ) at a frequency of 1 Hz of -10°C to 25.5°C and a biomass degree of 45% or more, the pressure-sensitive adhesive used in the pressure-sensitive adhesive layer is a (meth)acrylic pressure-sensitive adhesive containing an acrylic copolymer made of a (meth)acrylate alone or a copolymer of a (meth)acrylate and another monomer, An adhesive tape having a biomass content of 45% or more.

2. An adhesive layer containing 50 to 150 parts by mass of a rosin-based tackifier resin relative to 100 parts by mass of adhesive resin solids, the temperature showing a peak value of loss tangent (tan δ) at a frequency of 1 Hz being -10°C to 50°C, the pressure-sensitive adhesive used in the pressure-sensitive adhesive layer is a (meth)acrylic pressure-sensitive adhesive containing an acrylic copolymer made of a (meth)acrylate alone or a copolymer of a (meth)acrylate and another monomer, An adhesive tape having a 180 degree peel strength from a stainless steel plate of 28.3 N / 25 mm or more, as measured in accordance with JIS Z0237, and a biomass content of 45% or more.

3. 3. The pressure-sensitive adhesive tape according to claim 1, wherein the (meth)acrylate is an alkyl (meth)acrylate, and the alkyl group of the alkyl (meth)acrylate has 1 to 18 carbon atoms.

4. The pressure-sensitive adhesive tape according to any one of claims 1 to 3, wherein the tackifier resin has a biomass degree of 50% or more.

5. The pressure-sensitive adhesive tape according to any one of claims 1 to 4, comprising two or more types of tackifier resins.

6. The pressure-sensitive adhesive tape according to any one of claims 1 to 5, wherein the acrylic copolymer has a weight average molecular weight of 400,000 or more.

7. The pressure-sensitive adhesive tape according to any one of claims 1 to 6, wherein the pressure-sensitive adhesive layer has a gel fraction of 10% to 50%.

8. The pressure-sensitive adhesive tape according to any one of claims 1 to 7, wherein the pressure-sensitive adhesive layer has a thickness of 5 to 200 µm.

Citation Information

Patent Citations

  • Acrylic block copolymer composition

    JP2005307063A

  • Pressure-sensitive adhesive product and transfer tool

    JP2006206624A

  • Acrylic transparent pressure sensitive adhesive composition

    JP2009102467A

  • Binder for automobile interior material and binding sheet for automobile interior material

    JP2014189656A

  • JPP7290019B